A Study Of Early Enteral Feeding Versus Nil By Mouth In Case Of Resection Anastomosis Or Perforation Primary Repair (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background ; A period of starvation (“nil by mouth”- NBM) is common practice after gastrointestinal  surgery during which an intestinal anastomosis has been formed. So Early Entearl Feeding requires  scrutiny in the term of indications ,success and failure to give benefit to patient.  Methodology; The study is carried out on in patients admitted in municipal general hospital of  Ahmedabad . A total of 34 patients of intestinal resection anastomosis and perforation primary repair  were included in the study and data were collected in the prescribed performa consisting details of  patient’s history , clinical findings, operative findings, post operative course and complications, and  outcome. Results ; Observation and analysis of the data of present series was interesting and  important aspects were compared with standard series .Wound Infection was Common Complication  in both group .Morbidity and Other Complications were significantly low in early Enteral feeding  Group Patients. Conclusion; Early enteral feeding is safe, effective, feasible and cost effective in post  operative patients of resection and anastomosis or perforation primary repair.
Keywords: Enteral Feeding; resection and anastomosis